Implementasi Pembelajaran Problem Based Learning dengan Media Kartu Soal Untuk Meningkatkan Kemampuan Belajar Peserta Didik Mata Pelajaran PPKn kelas XI AKL 1 di SMK Negeri 1 Rejotangan - Hana Pertiwi; Muhamad Abdul Rozig Asrori (Lembaga Pengembangan Kinerja Dosen, 2024)
Education is a conscious and planned effort to increase the potential of human resources through learning activities aimed at helping students develop all their potential and personal characteristics in a better direction. (Herdiansyah et al., 2021). The learning process is expected to enable students to improve their knowledge, attitudes and skills which are very important for achieving educational goals Types of Research Classroom Action Research (PTK) is a type of research carried out by teachers in their own classes by (1) planning, (2) implementing, and (3) reflecting on actions carried out collaboratively and participatively with the aim of improving their performance as teachers and improve student learning outcomes. Classroom action research is a type of research that aims to improve the quality of learning and includes increasing knowledge about values that can ultimately be applied, as well as increasing student activity and creativity.From the results of the analysis of the results of classroom action research conducted at SMK Negeri 1 Rejotangan to improve PPKn learning outcomes for class This is indicated by a positive increase for each variable studied. The results of classroom action research show an increase in learning outcomes. Problem-based learning (PBL) in Civics subjects can improve learning outcomes. The results of the first cycle of research, with an average of 70 results, showed that only 13 students (or 32.5% of the total students) and 27 students (or 67.5% of the total students) did not reach the Minimum Completeness Criteria (KKM) for PPKn subjects of 75% . As a result, researchers had to continue the research to cycle II. After being implemented and improved, the problem-based learning (PBL) model was used in the second cycle of relearning actions. PPKn learning outcomes increased with an average score of 86 and a classical completion rate of 100%, with 40 students completing and 0 students not yet completing. Thus, researchers do not need to continue to the next cycle because student learning outcomes have reached the expected KKM scores and criteria.